Effects of lactoferrin, a protein present in the female reproductive tract, on parameters of human sperm capacitation and gamete interaction - Zumoffen, Carlos María (2015)
In a recent study, lactoferrin (LF) was detected in human oviductal secretion. The protein was able to bind to oocytes and sperm, and modulated gamete interaction. The aim of the present study was to investigate the effect of LF on parameters related to human sperm capacitation and sperm-zona pellucida interaction. Semen samples were obtained from healthy normozoospermic donors (n = 7). Human follicular fluids and oocytes were collected from patients undergoing in vitro fertilization. Motile sperm obtained by swim-up were incubated for 6 or 22 h under capacitating conditions with LF (0-100 μg/mL). After incubations, viability, motility, presence of α-d-mannose receptors (using a fluorescent probe on mannose coupled to bovine serum albumin), spontaneous and induced acrosome reaction (assessed with Pisum sativum agglutinin conjugated to fluorescein isothiocyanate), and tyrosine phosphorylation of sperm proteins were evaluated. Sperm-zona pellucida interaction in the presence of LF was investigated using the hemizone assay. The presence of LF did not affect sperm viability or motility, but caused a dose-dependent significant decrease in sperm α-d-mannose-binding sites, and the effect was already significant with the lowest concentration of the protein used after 22 h incubation. Dose-dependent significant increases in both induced acrosome reaction and tyrosine phosphorylation of sperm proteins were observed in the presence of LF. The present data indicate that LF modulates parameters of sperm function. The inhibition of gamete interaction by LF could be partially explained by the decrease in sperm d-mannose-binding sites. The presence of the LF promoted sperm capacitation in vitro.